THE EFFECT OF FINANCIAL PERFORMANCE AND GROWTH OPPORTUNITY ON INVESTMENT DECISIONS IN FOOD AND BEVERAGE COMPANIES IN INDONESIA STOCK EXCHANGE - Yulia Tri Kusumawati (Jurnal Ekonomi dan Manajemen, 2020)
This study aims to analyze the effect of Liquidity, Debt to Asset, Asset Turnover, and Growth on Investment Decisions in Food and Beverage Companies in the Indonesia Stock Exchange. The sample in this study are Food and Beverage group companies listed on the Indonesia Stock Exchange in the period 2013-2017. Sample selection is done by using purposive sampling method. This type of research is included in causal research with quantitative methods. The analytical tool used is a method of multiple regression analysis, classic assumption test, and hypothesis testing (t-test) using SPSS 22. The results show that partially, Liquidity and Growth Opportunity have a negative and significant effect on Investment Decisions, while Debt Asset and Asset Turnover has a negative and insignificant effect on Investment Decisions. Simultaneously, the Liquidity variable, Debt to Asset, Asset Turnover, and Growth have no significant effect on Investment Decisions.